The changing dynamics of short-run output adjustment - Korkut A. Ertürk; Ivan Mendieta-Mu\~noz (The University of Utah, Department of Economics, 2018)
Much of macroeconomic theorizing rests on assumptions that define the short-run output adjustment of a mass-production economy. The demand effect of investment on output, assumed much faster than its supply effect, works through employment expanding pari passu with changes in capacity utilization while productivity remains constant. Using linear Structural VAR and Time-Varying Parameter Structural VAR models, we document important changes in the short-run output adjustment in the USA. The link between changes in employment, capacity utilization and investment has weakened, while productivity became more responsive following demand shifts caused by investment since the early 1990s.
Keywords: B50; E10; E32; 330; Changes in short-run output adjustment; capacity utilization; employment; mass-production economy; post-Fordism